From ideology to performance: Austerity and government defection in the 2014 European Parliament elections - Magalhães, Pedro (2017)
The notion that domestic responses to financial crises are constrained in a way that limits the options available to national governments is not new. However, the last term of the European Parliament was a period when this reality was brought home to European electorates with previously unseen potency. This study explores the implications of this for the logic of voting in the 2014 European elections. Defection from government parties in EP elections is known to result from a combination of sincere/ideological and performance/protest voting logics. However, this study argues that fiscal tightening policies functioned, in the most affected countries, as a signal leading voters to discount the ideological positions of parties and to behave mostly under a pure protest logic.